2022
DOI: 10.1007/s12665-022-10213-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of arsenic mobility by organic matter in mining-impacted sediment from sub‐Arctic lakes: implications for environmental monitoring in a warming climate

Abstract: Arsenic (As) is commonly sequestered at the sediment–water interface (SWI) in mining-impacted lakes through adsorption and/or co-precipitation with authigenic iron (Fe)-(oxy)hydroxides or sulfides. The results of this study demonstrate that the accumulation of organic matter (OM) in near-surface sediments also influences the mobility and fate of As in sub-Arctic lakes. Sediment gravity cores, sediment grab samples, and porewaters were collected from three lakes downstream of the former Tundra gold mine, Northw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Arsenic is commonly sequestered at the sediment–water interface in mining-impacted lakes through adsorption and/or co-precipitation with authigenic Fe-(oxy)hydroxides or sulfides. A report by Miller et al 47 found that the accumulation of organic matter in near-surface sediments also influences the mobility and fate of As in sub-Arctic lakes. Sediment gravity cores, sediment grab samples, and porewater were collected from three lakes downstream of the former Tundra Au mine, Northwest Territories, Canada.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…Arsenic is commonly sequestered at the sediment–water interface in mining-impacted lakes through adsorption and/or co-precipitation with authigenic Fe-(oxy)hydroxides or sulfides. A report by Miller et al 47 found that the accumulation of organic matter in near-surface sediments also influences the mobility and fate of As in sub-Arctic lakes. Sediment gravity cores, sediment grab samples, and porewater were collected from three lakes downstream of the former Tundra Au mine, Northwest Territories, Canada.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…In mining-impacted lakes, As is commonly sequestered at the sediment through adsorption and/or co sulphides (Miller et al, 2022). A mobile and toxic than As(III) under soil oxidizing conditions, because it is strongly adsorbed to Fe hydroxides of soil (Álvarez discharge and natural sources release heavy metals in soil and food crops for animal and human intake (Srivastava et al, 2017).…”
Section: Arsenic Exposure From Thementioning
confidence: 99%
“…impacted lakes, As is commonly sequestered at the sediment-water interface through adsorption and/or co-precipitation with authigenic iron Fe-oxyhydroxides or sulphides (Miller et al, 2022). Arsenate [As(V)] is the predominant form of As and is less mobile and toxic than As(III) under soil oxidizing conditions, because it is strongly adsorbed to Fe hydroxides of soil (Álvarez-Robles et al, 2020).…”
Section: Arsenic Exposure From Thementioning
confidence: 99%